Sistem Informasi Pelayanan Publik Berbasis Website di Kantor Desa Tawang Bengkayang - Patia Mega; Wina Yusnaeni (Universitas Bina Sarana Informatika, 2026)
The development of information technology has driven digital transformation across various sectors, including in village governance. The Tawang Village Office in Bengkayang District still relies on a manual public service system. This has led to several problems, such as delays in administrative processes, lack of transparency, and limited access to information for the public. These issues hinder service efficiency and reduce community satisfaction with the performance of the villagegovernment.The aim of this study is to develop and implement a web-based Public Service Information System that can accelerate administrative services such as the issuance of Certificates of Domicile, Certificates of Inability (SKTM), and other administrative documents. Data collection methods used in this study include interviews, direct observation, and literature review. The system was developed using the Waterfall software development method, which consists of five main phases: requirements analysis, system design, implementation, testing, and maintenance.The results of the system implementation show that the use of this. information system significantly improves the efficiency and effectiveness of public services at the Tawang Village Office. Residents can now access services online via desktop or mobile devices using modern web browsers. Although the system is digitally based, manual verification by village officials is still maintained to ensur the validity of documents.